U.S.-China Rivalry Controls AI-Based Defense Machine in the Natuna Sea and Malacca Strait: Indonesia's AI Governance Diplomacy in Navigating International Regulations - Baresi, Muhammad Jordan; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This research examines the intensifying military artificial intelligence (AI) rivalry between the United States and China in the Southeast Asian maritime domain, with a focus on its implications for Indonesia’s sovereignty and regional security, particularly in the Natuna Sea and the Strait of Malacca. Despite the strategic significance of this technological contest, its impact on Indonesia’s defense and diplomatic posture remains underexplored. The study aims to analyze how the U.S.–China military AI competition is reshaping regional security dynamics and how Indonesia’s defense diplomacy navigates international legal frameworks amid emerging AI-based threats. Adopting a qualitative descriptive approach with a comparative case study design, the research draws on diplomatic documents and reports from international institutions such as the UN, ASEAN, SIPRI, and IISS. Data were analyzed using thematic coding via NVivo 14 and triangulated across multiple sources. Findings reveal that military AI has transformed conventional security concerns into an era of algorithmic rivalry that remains largely unregulated under existing international law. In response, Indonesia has pursued a form of AI Governance Diplomacy, a defense diplomacy strategy grounded in the principles of human oversight, algorithmic transparency, and legal accountability. The study concludes that Indonesia’s normative approach contributes to shaping emerging global norms on military AI governance. Theoretically, the findings expand non-traditional security discourse by incorporating algorithmic threats, while practically offering recommendations to strengthen ethical and regulatory frameworks for AI within ASEAN’s regional security architecture.